2017
DOI: 10.1371/journal.pone.0179737
|View full text |Cite|
|
Sign up to set email alerts
|

Serum fatty acid-binding protein 4 (FABP4) concentration is associated with insulin resistance in peripheral tissues, A clinical study

Abstract: Type 2 diabetes mellitus (T2DM) is caused by insulin resistance and β cell dysfunction. In recent studies reported that several markers associated with insulin sensitivity in skeletal muscle, Adiponectin and other parameters, such as fatty acid-binding protein (FABP4), have been reported to regulate insulin resistance, but it remains unclear which factor mostly affects insulin resistance in T2DM. In this cross-sectional study, we evaluated the relationships between several kinds of biomarkers and insulin resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 38 publications
(50 reference statements)
2
45
0
1
Order By: Relevance
“…Increases in basal FABP-4 levels have been reported in obesity and insulin resistant states [4]. We found that clinically relevant hyperinsulinemia significantly suppressed levels of FABP-4 by approximately 18%.…”
Section: Statement Of Author's Contributionssupporting
confidence: 64%
See 3 more Smart Citations
“…Increases in basal FABP-4 levels have been reported in obesity and insulin resistant states [4]. We found that clinically relevant hyperinsulinemia significantly suppressed levels of FABP-4 by approximately 18%.…”
Section: Statement Of Author's Contributionssupporting
confidence: 64%
“…Check for updates chemokines [1][2][3][4][5]. These chemokines are reported to be altered in insulin resistance and have even been proposed to mediate of some of the features of insulin resistance [2][3][4][5].…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a direct insulinotropic action of FABP4, a cytosolic lipid chaperone expressed and secreted by white and brown adipocytes may act directly on pancreatic beta cells as demonstrated in previous studies showing that recombinant FABP4 administration enhanced glucose-stimulated insulin secretion in vitro and in vivo [41,42]. In a small type 2 diabetes cohort, increased serum FABP4 was correlated to enhanced insulin release [43]. Taking these findings together, lowered circulating incretins may have provoked impaired glucose tolerance with no apparent change in beta cell function to release insulin in vivo-compensated by stimulation of glucose-stimulated insulin secretion by higher circulating FABP4 and NEFA-in aTCF7L2KO mice.…”
Section: Discussionmentioning
confidence: 78%